Comparison of Steady State and Dynamic Interaction Measurements in Multiloop Control Systems - Renanto Handogo; Avon T. H.; Joko Lelono (Department of Chemical Engineering, Universitas Gadjah Mada, 2005)
The applicability of the steady-state Relative Gain Array (RGA) to measure dynamic process interactions in a multiloop control system was investigated. Several transfer function matrices were chosen, and the gains, time constants, and dead times of their elements were varied to represent the systems with dominant dynamic interactions. It was shown that the steady-state RGA method predicted the controller pairing accurately if the pairing elements recommended by RGA had the bigger gains and the same or smaller time constants compared to other elements in the corresponding rows. When these conditions were not met, the RGA would give a wrong result, and dynamic interaction measurements, such as the Average Dynamic Gain Array (ADGA) and the Inverse Nyquist Array (lNA), should be used instead to determine the best controller pairing in a multiloop control system. Keywords: Control pairing, dynamic process interaction, multiloop control systems, Relative Gain Array (RGA), and steady state.